ALMA uncovers the [C ii] emission and warm dust continuum in a z = 8.31 Lyman break galaxy. Issue 3 (5th March 2020) - Bakx, Tom J L C; Tamura, Yoichi; Hashimoto, Takuya; Inoue, Akio K; Lee, Minju M; Mawatari, Ken; Ota, Kazuaki; Umehata, Hideki; Zackrisson, Erik; Hatsukade, Bunyo; Kohno, Kotaro; Matsuda, Yuichi; et al.
ABSTRACT: We report on the detection of the [C ii ] 157.7 μ m emission from the Lyman break galaxy (LBG) MACS0416_Y1 at z = 8.3113, by using the Atacama Large Millimeter/submillimeter Array (ALMA). The luminosity ratio of [O iii ] 88 μ m (from previous campaigns) to [C ii ] is 9.3 ± 2.6, indicative of hard interstellar radiation fields and/or a low covering fraction of photodissociation regions. The emission of [C ii ] is cospatial to the 850 μ m dust emission (90 μ m rest frame, from previous campaigns), however the peak [C ii ] emission does not agree with the peak [O iii ] emission, suggesting that the lines originate from different conditions in the interstellar medium. We fail to detect continuum emission at 1.5 mm (160 μ m rest frame) down to 18 μ Jy (3σ). This non-detection places a strong limits on the dust spectrum, considering the 137 ± 26 μ Jy continuum emission at 850 μ m. This suggests an unusually warm dust component ( T > 80 K, 90 per cent confidence limit), and/or a steep dust-emissivity index (βdust > 2), compared to galaxy-wide dust emission found at lower redshifts (typically T ∼ 30–50 K, βdust ∼ 1–2). If such temperatures are common, this would reduce the required dust mass and relax the dust production problem at the highest redshifts. We therefore warn against the use of only single-wavelength information to derive physical properties, recommend a more thorough examination of dust temperatures in the early Universe, and stress the need for instrumentation that probes the peak of warm dust in the Epoch of Reionization.